ChemInform Abstract: 6, 7‐seco‐ent‐Kaurane Diterpenoids from Isodon sculponeatus and Their Bioactivity. Issue 38 (10th September 2014) - Jiang, Hua‐Yi; Wang, Wei‐Guang; Zhou, Min; Wu, Hai‐Yan; Zhan, Rui; Du, Xue; Pu, Jian‐Xin; Sun, Han‐Dong
Abstract Sculponin T (I) is isolated from the aerial parts of Isodon sculpneatus along with four known analogs.